優先動的結晶粒成長機構によるFe-Mn-Si-Cr合金の集合組織制御と形状記憶特性の向上 - 福富, 洋志; 中島, 格; 長谷川, 誠; 鈴木, 茂; 岡安, 和人; 小貫, 祐介 (鉄と鋼, 2021)
The development of cube texture in Fe-Mn-Si-Cr shape memory alloy by the preferential dynamic grain growth mechanism is experimentally examined. The plane strain compression deformation at 1173 K with strain rates of 2.0 × 10−3 s−1, 1.0 × 10−3 s−1, and 5.0 × 10−4 s−1 results in the development of cube texture. The maximum volume fraction of cube orientated grains is about 25% which is ten times as high as that before the deformation. It is experimentally confirmed that the specimen with {001}(surface of the tensile specimens) (tensile direction) shows higher shape memory efficiency than those prepared by the so called training treatment. The texture evaluation by neutron diffraction method elucidates that control of the texture in the γ single phase state is effective to specify the active shear system contributing to the shape memory effect.